2013
DOI: 10.1249/mss.0b013e3182980125
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Parasympathetic Hyperactivity in Functionally Overreached Athletes

Abstract: Using daily HRV recordings averaged over each week, this study detected a progressive increase in the parasympathetic modulation of HR in endurance athletes led to F-OR. It also revealed that due to a wide day-to-day variability, isolated, once per week HRV recordings may not detect training-induced autonomic modulations in F-OR athletes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
199
1
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(219 citation statements)
references
References 47 publications
9
199
1
10
Order By: Relevance
“…45 Indeed, HRex during intensified training intensities showed significant reductions in overreached triathletes. Le Meur et al 46,47 suggested the cause of this reduction in heart rate to be a hyperactivation of the parasympathetic nervous system via central, cardiac, and/or periphery mechanisms. In contrast to Le Meur et al, 46,47 the results of the current study suggest, although, speculative, an acute stimulation of the sympathetic nervous system thus increasing HRex after a short continued period of training.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…45 Indeed, HRex during intensified training intensities showed significant reductions in overreached triathletes. Le Meur et al 46,47 suggested the cause of this reduction in heart rate to be a hyperactivation of the parasympathetic nervous system via central, cardiac, and/or periphery mechanisms. In contrast to Le Meur et al, 46,47 the results of the current study suggest, although, speculative, an acute stimulation of the sympathetic nervous system thus increasing HRex after a short continued period of training.…”
Section: Discussionmentioning
confidence: 99%
“…Le Meur et al 46,47 suggested the cause of this reduction in heart rate to be a hyperactivation of the parasympathetic nervous system via central, cardiac, and/or periphery mechanisms. In contrast to Le Meur et al, 46,47 the results of the current study suggest, although, speculative, an acute stimulation of the sympathetic nervous system thus increasing HRex after a short continued period of training. Indeed, in both recreational marathon runners and world-class rowers, a significant increase in sympathetic dominance following a training block in the lead up to competition has been observed.…”
Section: Discussionmentioning
confidence: 99%
“…Heart rate during intensified training and during varying intensities showed significant reductions in overreached triathletes. Le Meur et al 28,30,31 suggested a hyperactivation of the parasympathetic nervous system via central, cardiac and/ or periphery mechanisms. Recent observations in AFL have also reported reductions in heart rate in response to training during preseason, although, the authors concluded this was more possibly due to the effects of training/environmental induced changes in plasma volume than acute changes in fitness or fatigue.…”
Section: Submaximal Heart Ratementioning
confidence: 99%
“…Особенностью физиче-ской реабилитации у больных является исходно не-высокое функциональное состояние, поэтому при неадекватных нагрузках у них также могут возни-кать признаки перегрузки, проявляющиеся сниже-нием толерантности при повторных нагрузочных тестах [9]. Поскольку сдвиг вегетативного баланса в сторону симпатической активации может быть од-ним из ранних признаков неадекватности ФТ [10], то будет логичным использовать данный подход для контроля эффективности реабилитационных меро-приятий у пациентов [7,[11][12][13]. В этих целях при-меняется оценка вариабельности ритма сердца (ВРС) как при суточном мониторировании электро-кардиографии (ЭКГ) [9], так и на коротких участках записи [12], однако широкого практического при-менения данные методики не находят.…”
Section: сведения об авторахunclassified